E-Perpus SMA Negeri 1 Cengal Menggunakan Metode Extreme Programming - Renaldi Agustian Hamzah; Syahril Rizal (LPPM STIKOM Tunas Bangsa, 2024)
A library is an institution or place that has an important role in providing access to various types of information, knowledge and reading materials. High school libraries have a very crucial background as providers of learning resources which provide various types of learning resources including textbooks, references, journals, magazines and digital materials. These learning resources support students in various subjects and encourage them to understand the concept of the learning process better. Currently, the library at SMA Negeri 1 Cengal is currently searching for references in the form of books or other reading sources done manually, namely by involving library staff to look for books that visitors want to borrow or the borrowing process is still carried out using a manual recording process with large books. In this research the author used the extreme programming (XP) method. To overcome the problems mentioned above. Researchers used Extreme Programming techniques in the Agile Methods methodology to build this library information system. The development process is simplified with Extreme Programming, which makes it more adaptable and versatile. It also offers alignment with design and functionality changes, and is easy to handle.